Copper–Ammonia–Thiosulfate Leaching of High-Sulfide Concentrates: Process Optimization and Additive Effects on Gold Extraction - Azizbek Bolikulovich Buronov; Blackie Korul Yayabu; Labone Lorraine Godirilwe; Batnasan Altansukh; Sanghee Jeon; Kazutoshi Haga; Atsushi Shibayama (Metals, 2025)
This research focuses on finding an environmentally friendly method for extracting gold from a sulfide flotation concentrate. In this study, an ammonia–copper–thiosulfate leaching system was utilized for the extraction of gold. The flotation concentrate sample contains about 190 ppm of gold, 160 ppm of silver, and 6.89% of copper. To achieve an optimized gold extraction, various parameters, such as thiosulfate, ammonia and copper concentrations, pulp density, pH, stirring rate, temperature, and time, were investigated. About 87% of gold was leached under the following conditions: 0.5 M S2O32−, 1.0 M NH3, 0.1 M Cu2+, a stirring rate of 350 rpm, a pH of 12, a pulp density of 10% solids, a temperature of 25 °C, and a leaching time of 2 h. Additionally, to improve the economic effectiveness of the leaching system, thiosulfate consumption was investigated by utilizing different additives, such as diethylenetriamine (DETA), glycerol, and ammonium dihydrogen phosphate (ADP). The results showed that with the use of ADP, gold extraction increased from 87% to 91% while reducing copper dissolution. Additionally, the thiosulfate consumption also decreased from 0.37 M to 0.3 M. The inclusion of ADP was particularly effective, enhancing gold extraction efficiency and reducing reagent consumption, thereby making the process more sustainable. Considering the high economic value of gold, the optimization of recovery efficiency is prioritized over reagent costs in this study. Overall, this study indicates that the optimized ammonia–copper–thiosulfate leaching system with ADP additive is a promising environmentally friendly method for the extraction of gold.